Inhibition of monocyte, lymphocyte, and neutrophil adhesion to endothelial cells by human milk oligosaccharides - Bode, Lars; Kunz, Clemens; Muhly-Reinholz, Marion; Mayer, Konstantin; Seeger, Werner; Rudloff, Silvia (Thrombosis and Haemostasis, 2004)
Excessive leukocyte infiltration causes severe tissue damage in a variety of inflammatory diseases. The initial step in leukocyte extravasation is mediated by selectins and oligosaccharides on their glycoconjugate ligands. Human milk is a rich source of lactose-derived oligosaccharides that are partly absorbed in the intestine and excreted with the urine. As these components contain binding determinants for the selectins we investigated whether human milk oligosaccharides are able to affect leukocyte rolling and adhesion to endothelial cells under dynamic conditions. Therefore, monocytes, lymphocytes, or neutrophils isolated from human peripheral blood were passed over TNF-α-activated HUVEC under shear stress. The influence of different oligosaccharide fractions was determined by video-micros-copy and compared with the effects of various individual oligosaccharides. Within a physiological range (12.5-125 µg/ml) the acidic fraction significantly inhibited leukocyte rolling and adhesion (up to 24.0% and 52.8%, respectively) in a concentrationdependent manner. These effects were even more pronounced than those achieved by soluble sialyl-Lewis x, a physiological binding determinant for selectins. Several active components within the oligosaccharide fraction of human milk were identified, e.g. 3’-sialyl-lactose and 3’-sialyl-3-fucosyl-lactose. These results indicate that specific oligosaccharides in human milk may serve as anti-inflammatory components and might therefore contribute to the lower incidence of inflammatory diseases in human milk-fed infants.
Keywords: Selectins; leukocytes; oligosaccharides; human milk; inflammation